Development of an anthropomorphic spine phantom suitable for fusion of MR neurography with interventional flat-panel CT. Issue 112 (March 2019) - Kobe, Adrian; Zadory, Matthias; Hamie, Qeumars M.; Froehlich, Johannes M.; Klarhöfer, Markus; Elsässer, Thilo; Pfammatter, Thomas; Guggenberger, Roman
Abstract: Purpose: To design a spine phantom suitable for fusion of MR neurography (MRN) with interventional flat panel computed tomography (FPCT) images from tissue-equivalent agarose gels and artificial nerves in MRI, including material with equal attenuation to bone in computed tomography (CT). Methods: T1-/T2-relaxation times of target tissue were determined in vivo (n = 5) using MR mapping-techniques. Serial dilution of castor oil lipogels was performed ex vivo in order to define correct composition for tissue-equivalent relaxation times. Similarly, serial dilution series of calcium carbonate (CaCO3 ) and barium sulphate (BaSO4 ) in synthetic resin were used to adjust radiodensity of selected vertebral bodies (L1-L5) and sacrum in CT. Nerve tissue was simulated with agarose-impregnated polyethylene fibers. Spine phantom was assembled using respective components in anthropomorphic geometry. A fat-saturated, T2-weighted 3D SPACE STIR sequence was acquired for MRN and subsequently fused with an on-site FPCT scan of the phantom. Results: In vivo T1-/T2-values for fat tissue were found to be at 394 ± 16 ms and 161 ± 16 ms, corresponding to a castor oil concentration of 50%. Analogously, bone marrow-equivalent values were measured at 822 ± 21 ms and 67 ± 6 ms, simulated with 40% castor oil. Cortical bone-like radiodensity of 1'115 ± 80 HU was achieved for artificial bone with 30% CaCO3 and 1.5% BaSO4 . Simulated nerves were successfully depicted in MRN and fused with FPCT, combining optimal contrasts for nerves and bones on-site. Conclusions: The customized phantom showed analogous tissue contrasts to in vivo conditions in both MRN and FPCT, facilitating simulations of fusion-image guided spine interventions.